Toward an economic sociology of race. (19th December 2019) - Hirschman, Daniel; Garbes, Laura
Abstract: Race is central to economic life, but race is not central to economic sociology. We argue that economic sociologists should treat racism as a constitutive, structuring force, analytically co-equal with capitalism, patriarchy and nationalism. Our article has three aims. First, we document how canonical and award-winning works of economic sociology do not discuss race and racism, and do not engage with the contemporary sociology of race. Second, we identify six key insights from the sociology of race and suggest how they could influence economic sociology: the emergence of race out of racism, an understanding of racism as structural, the role of whiteness, the intersections between racism and other systems of oppression, the ideology of colorblind racism and the fundamental connections between racism and capitalism. Third, we conclude by discussing recent research that bridges the two subfields and lays the groundwork for an understanding of 'racialized markets' and 'racialized economies'.